Adam Watkins' 9th Birthday Party in Backyard - Watkins, Howard::::::::: (1987)
Maya Armstrong, Josiah Gordon, Elizabeth Nowlis, Stephanie Leifer, ?, Jared Gordon, Gregory Leifer, Marshall Chambers (wearing glasses), Dakota Iyall, Art Wille and Adam Watkins